COMPUTER IMAGE PROCESSING OF MICROSTRUCTURES OF GRAY CAST IRON AS A TOOL FOR QUANTITATIVE ANALYSIS OF GRAPHITE DISTRIBUTION - A. N. Chichko; O. A. Sachek; S. G. Lihouzov; O. I. Chichko (Литьë и металлургия)
Based on gray cast iron microstructure with different lengths of flaky graphite inclusions contained in GOST 3443-87 «Cast iron with various forms of graphite. Methods for determining the structure «shows the possibilities of classification of microstructures ПГд15, ПГд25, ПГд45, ПГд90, ПГд180, ПГд350, ПГд750 and ПГд1000 based on image processing techniques that allows to develop a methodology for the transition from qualitative scale of microstructures used for the analysis of the graphite phase, to quantify.